2005
DOI: 10.1136/gut.2004.043059
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm within diseased pancreatic and biliary tracts

Abstract: Background: Bacterial community structures in human pancreatic and biliary tracts were evaluated. Methods: Gall bladder stones from 153 patients, 20 gall bladder walls, six common duct stones, 52 biliary stents, 21 duodenal biopsies, nine pancreatic duct biopsies, and five bile ducts were investigated using fluorescence in situ hybridisation (FISH) with ribosomal RNA targeted Cy3/Cy5 (carbocyanine) labelled oligonucleotide probes. Result: Duodenal, gall bladder, and bile duct walls were free of bacteria. A den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 26 publications
(9 reference statements)
3
48
0
5
Order By: Relevance
“…This is in part because of the difficulties in constructing bacterial strains deficient in lipoprotein production due to its high abundance and the deleterious effects of these mutations on bacteria. Bacteria form biofilms to provide protection from environmental insults in various niches, including the gastrointestinal tract (78)(79)(80)(81). Bacterial species express amyloid fibrils as a major component of their extracellular matrix in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…This is in part because of the difficulties in constructing bacterial strains deficient in lipoprotein production due to its high abundance and the deleterious effects of these mutations on bacteria. Bacteria form biofilms to provide protection from environmental insults in various niches, including the gastrointestinal tract (78)(79)(80)(81). Bacterial species express amyloid fibrils as a major component of their extracellular matrix in biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported a high number of bacteria present in the calcified pancreatic duct epithelium and in pancreatic abscess (33-37). Some of the bacteria isolated from pancreatic tissues are also known members of the oral microbiome (34, 35, 38, 39). Bacterial dissemination from the mouth to the pancreas may include the colon via bacterial translocation, general circulation, biliary duct, duodenum, and the lymphatic system (33, 40-43).…”
Section: Pathogenic Microbiota: Evaluating Evidence For a Causal Linkmentioning
confidence: 99%
“…Using culture methods, the microbiota isolated from the pancreas had similarities to oral microbiota, particularly in the case of pancreatitis 8–11. Bacteria reaching the pancreatic tissues by dissemination has been documented in both animal models and human subjects 9 12 13. Additionally, multiple observations have shown that oral microbiota overlap with the digestive tract microbiota, providing multiple avenues for dissemination in dysbiosis 14–17.…”
Section: Introductionmentioning
confidence: 99%